FusionCharts beginners guide : the official guide for fusioncharts suite : create interactive charts in JavaScript (HTML5) and Flash for your web and enterprise applications - Nadhani, Sanket (Packt Pub., 2012)
The book is written as a practical, step-by-step guide to using FusionCharts Suite. The book not only teaches you the fundamentals and implementation of FusionCharts Suite, but also makes you the data visualization guru among your friends and colleagues by teaching how to select the right chart type and usability tips. Filled with examples, code samples and practical tips in a no-nonsense way, the book is a breeze to read. This book is both for beginners and advanced web developers who need to create interactive charts for their web applications. No previous knowledge of FusionCharts Suite is a.